Química con láseres - Marillo Sialer, Estephany (2017)
The number of applications of lasers in science is constantly growing, with applications stretching from chemistry, physics and materials science to biology and medicine. This article provides a short overview of the fundamentals of lasers and an introduction to the application of lasers and laser ablation in chemistry.